Taxpayer Awareness and Understanding on Taxpayer Compliance in Nepal - Adhikari, Naba Raj (Management Dynamics, 2020)
This study aims at examining the influence of taxpayer awareness and taxpayer understanding toward taxpayers’ compliance in Nepal. The research population is taxpayers that are registered in Inland Revenue Office, Nepalgunj. This study used convenience as well as purposive sampling as a sampling technique. A total number of 60 questionnaires were distributed to the taxpayers comprised with five point Likert scale with 1 for a highly disagreeable rate to 5 for a strongly agreed answer from Nepalgunj sub metropolitan during January to March 2020 AD. Out of these, 52 questionnaires were returned and accepted for data analysis. Descriptive statistical analysis and linear regression analysis have been applied as for the analysis of data. The findings of this study showed that the taxpayer awareness and understanding of tax have a positive and significant effect on taxpayer compliance. The taxpayer understanding have a stronger influence than a variable of taxpayer awareness. Therefore it is suggested that the tax office should enforce tax education programs to taxpayers regularly and continuously to increase the taxpayers’ understanding and awareness.